Heat conduction effect of steel bridge deck with conductive gussasphalt concrete pavement. (30th May 2018) - Wang, Chaohui; Chen, Qian; Fu, Hao; Chen, Jiao
Highlights: The heat conduction effect of conductive gussasphalt concrete was evaluated. Estimation equations of heat conduction effect were derived and verified. The time required to maintain the surface temperature above 0 °C was determined. Abstract: The snow- and ice-melting effect and energy usage of steel bridge deck pavement are affected by the heat-transfer rate and temperature change in the middle of the combination structure when using conductive gussasphalt concrete (CGA). To determine the heat conduction effect and the snow melting time of conductive gussasphalt concrete pavement, the heat conduction estimation method and a theoretical equation of the CGA combination structure are derived. A CGA combination structure with spreading carbon fiber in the middle of the CGA layer is prepared. The accuracy of the theoretical equation is checked and verified. Then, the heat conduction effect and the time required to reach and maintain the temperature above 0 °C of different CGA combination structures are evaluated. According to the estimation results and weather conditions, the power will be turned on or shut off ahead of time to improve the deicing efficiency and save energy. The results show that the theoretically obtained estimation values are close to the test values. The theoretical equation can estimate the heat conduction effect of the CGA combination structure. With a decrease in the environmental temperature, the time required for the surface temperature of different CGA combination structures to exceed 0 °C gradually increases, and the time required for the surface temperature to remain above 0 °C decreases. The surface temperatures of the CGA combination structure based on schemes 3 and 4 can be increased to above 0 °C in a short time and remain above 0 °C for a long time.